Experimental study on the temperature-sensitive behavior of poly-n-isopropylacrylamide/graphene oxide composites and the flexible conductive cotton fabrics. (June 2022) - Tan, Jinhong; Yang, Qun; Hu, Genghao; Zhang, Hongjuan; Pei, Liujun; Wang, Jiping
Abstract: This work focused on the development and characterization of poly-n-isopropylacrylamide/graphene oxide composite (PNIPAM-GO) which was prepared by in situ free radical polymerization of n-isopropylacrylamide and graphene oxide (GO). It was then compounded on cotton fabrics by dip-drying layer group method to prepare PNIPAM-GO/cotton fabrics, which were further reduced by hydrazine hydrate to obtain PNIPAM-rGO/cotton conductive fabrics. The conductivity of flexible conductive fabrics and performance of PNIPAM-GO composite were studied by scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. The results show that PNIPAM-GO composites have reversible temperature-sensitive response, the lower critical solution temperature (LCST) of PNIPAM-GO composites increased with the introduction of GO. With increasing of dip-drying cycles, the resistance value of PNIPAM-rGO/cotton fabrics decreased, which decreased from 908.3 KΩ with 5 dip-drying cycle processes to 162.5 KΩ with 15 dip-drying cycle processes at 25 °C. Besides, PNIPAM-rGO/cotton fabrics have temperature-sensitive conductivity, the resistance value decreased when testing temperature above LCST. The results also show that the resistance value changed reversibly with the changing of testing temperature above or below the LCST of PNIPAM-GO. Therefore, PNIPAM-rGO/cotton fabrics have potential development in flexible conductive materials in temperature control valve. Highlights: Poly-n-isopropylacrylamide/graphene oxide composite with reversible temperature-sensitive response has been prepared. Dip-drying layer group technique has been applied on fabrics substrate. Flexible conductive fabric has reversible temperature-sensitive conductivity. Flexible conductive fabric has potential application in wearable temperature control valve.